Understanding business - Nickels, William G. (McGraw-Hill/Irwin, 2005)
Understanding Business by Nickels, McHugh, and McHugh has been the number one textbook in the introduction to business market for several editions for two reasons: (1) The commitment and dedication of an author team that teaches this course and believes in the importance and power of this learning experience and (2) We Listen. We consistently look to the experts – full-time faculty members, adjunct instructors, and of course students – to drive the decisions we make about the text itself and the ancillary package. Through a series of focus groups, symposia, as well as full-book, single-chapter, revised manuscript reviews of both text and key ancillaries, we have heard the stories of more than 400 professors and their insights and experiences are evident on every page of the revision. As teachers of the course and users of their own materials, the author team is dedicated to the principles of excellence in business education. From providing the richest most current topical coverage to using dynamic pedagogy that puts students in touch with today’s real business issues, to creating groundbreaking and market-defining ancillary items for professors and students alike, Understanding Business leads the way.